Least Cost Electricity Master Plan, Djibouti : Volume 1. Main Report - World Bank (Washington, DC, 2014)
Djibouti is characterized by a large urban population. About 70 per cent of the population lives in the main town of Djibouti-Ville, 11 per cent live in secondary towns and the remainder in a rural setting, including a substantial nomadic population. The country s electrification rate is about 50 per cent. Electricité de Djibouti (EdD), the national state-owned utility, report that there are approximately 38,000 electricity connections for the Djibouti-Ville metropolitan area. There is a total reliance on imported oil products as the fuels for electricity generation and the country has no hydroelectric potential. This has implied very high costs of production and of electricity generation in particular. Due to the high cost of electricity and high connection fees, the electrification rate remains relatively low and mostly available to the privileged, while performance of critical social and commercial sectors are hampered. The World Bank appointed Parsons Brinckerhoff (PB) to undertake engineering consultancy services for the preparation of an electricity sector least cost master plan for Djibouti. The objectives of the assignment are: To define the least-cost investment program for the development of Djibouti s electric generation, transmission and distribution system for the next 25 years, particularly taking into consideration the country s resources and recent economic and sector developments. Particular attention and detail should be given for the short-term forecast period (first 5 years) of the plan. To provide EdD and the Government of Djibouti (GoD) a comprehensive report, model and database for the further development of its systems and updates of the plan as needed. To provide EdD and the Ministry of Energy & Natural Resources (MENR) with some basic planning capacity and tools to update some key components of the master plan as needed. Volume 1 is the main report, and Volume 2 consists of appendices.